Consumer Protection as a Motorcycle Purchase that Suffers Damage during the Warranty Period - Devani Pane, Dwina (Riviera Publishing, 2025)
Aviation is a vital means of transportation that supports human mobility, where efficiency and punctuality (On Time Performance / OTP) are the main indicators of operational success. In this context, ramp handling operations, especially in handling emergency situations (crash handling), are a significant challenge that can interfere with the achievement of OTP. This study aims to analyze the operational effectiveness of ramp handling and identify obstacles related to crash handling at Kualanamu International Airport, in order to find strategic solutions to improve OTP. A descriptive qualitative approach was used through case studies, field observations, and in-depth interviews with operational officers of PT Gapura Angkasa, complemented by analysis of operational documents. The results of the study show that the limitations of equipment such as goods moving vehicles, fuel supply systems, and special baggage handling equipment, as well as the lack of trained manpower, especially in emergency situations, have a significant impact on the decrease in OTP. Suboptimal crash handling results in operational delays, thereby reducing flight efficiency and safety. The conclusion of this study states that improving resource management, both in terms of equipment and labor, as well as optimizing operational procedures is needed to overcome existing constraints. With these improvements, it is hoped that the achievement of OTP can increase significantly, support safety, efficiency, and quality of operational services at airports, thereby strengthening the competitiveness of the national aviation industry.